Taxonomic revision on the Gobio group in the Yellow River drainage, with discussion on the validity of the genus Acanthogobio (Cypriniformes, Gobionidae) - Yutian Fang; Zhixian Sun; Yahui Zhao (Zoosystematics and Evolution)
The Yellow River drainage is a biodiversity hotspot for the Gobio group, but no one has yet reviewed these species systematically. This study examined the type specimens of the species in the Gobio group and numerous newly captured specimens in the Yellow River drainage for an overall morphological comparison. A phylogenetic tree of those species based on mitochondrial cytochrome-b sequences was also constructed. Our results indicate the presence of four species, i.e., Gobio guentheri (this was described as Acanthogobio guentheri), G. rivuloides, G. coriparoides, and G. huanghensis. Morphological and molecular phylogenetic analyses indicated that G. tchangi is a junior synonym of G. huanghensis, while G. meridionalis is a junior synonym of G. rivuloides. Additionally, the phylogenetic analysis showed that the genus Acanthogobio is nested within Gobio. In order to maintain the monophyly of Gobio, this study suggests that the genus Acanthogobio should be a junior synonym of Gobio, and the type species A. guentheri should be treated as Gobio guentheri. Furthermore, the type specimens of Romanogobio johntreadwelli and R. amplexilabris were checked, and this study confirmed that these two species are junior synonyms of G. rivuloides. Therefore, the genus Romanogobio is not distributed in the Yellow River drainage. The Gobio species are primarily distributed in the upper and middle reaches of the Yellow River drainage, from Qushian Township, Qinghai Province, to Sanmenxia City, Henan Province, at an average elevation above 300 meters. A diagnostic key for four valid Gobio species in the Yellow River drainage is provided.